Implementation of Dhuha Prayer in Forming Student Character - Sugianti, Anggun; Mun'amah, Anatun Nisa; Munip, Al (Zabags International Journal of Education, 2023)
This research is a descriptive qualitative; the data collection was carried out using observation, interview, and documentation techniques. Then, after the data is collected, data analysis is carried out using data reduction techniques, data presentation, and a conclusion. The results of this study are (1) that through the implementation of the Duha prayer, the character values of class II students include religious character, responsibility, discipline, and independence. The implementation of the Duha prayer at MTs Raudhatul Hasanah Sabak Barat is carried out in the planning, implementation, and evaluation stages. Planning is in the form of preparing the necessary media in the form of a microphone, sound system, as well as methods for implementing the Duha prayer. The implementation includes the practice of ablution, the practice of dhuha prayer, and prayer and dhikr after prayer. Evaluation of the implementation of the Duha prayer can be done daily or monthly. Daily assessment can be seen from the attitudes and behavior of students. (2) Supporting factors for the implementation of Duha prayer in the formation of class II student character include the availability of supporting facilities and infrastructure, cooperation between all teachers and staff, and student enthusiasm. The inhibiting factors are the lack of a place to perform the Duha prayer, uncertain weather conditions, students who arrive late, and students who are too active.